2023
DOI: 10.1101/2023.10.11.561900
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational mechanisms underlying motivation to earn symbolic reinforcers

Diana C. Burk,
Craig Taswell,
Hua Tang
et al.

Abstract: Reinforcement learning (RL) is a theoretical framework that describes how agents learn to select options that maximize rewards and minimize punishments over time. We often make choices, however, to obtain symbolic reinforcers (e.g. money, points) that can later be exchanged for primary reinforcers (e.g. food, drink). Although symbolic reinforcers are motivating, little is understood about the neural or computational mechanisms underlying the motivation to earn them. In the present study, we examined how monkey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
1
0
0
Order By: Relevance
“…We found that OFC encoded accumulated tokens and changes in tokens at both the single-cell and population levels. These findings are consistent with previous work showing that OFC codes state information about the environment [37][38][39][40] , as tokens and token updates define states and state transitions in this task 41 . State representation is also referred to as a cognitive map, particularly when states have to be inferred 42,43 .…”
Section: Ofc Contributes To the Encoding Of Symbolic Reinforcerssupporting
confidence: 92%
“…We found that OFC encoded accumulated tokens and changes in tokens at both the single-cell and population levels. These findings are consistent with previous work showing that OFC codes state information about the environment [37][38][39][40] , as tokens and token updates define states and state transitions in this task 41 . State representation is also referred to as a cognitive map, particularly when states have to be inferred 42,43 .…”
Section: Ofc Contributes To the Encoding Of Symbolic Reinforcerssupporting
confidence: 92%